Synthesis and antitumor properties of some new N-(5-R-benzyl-1,3-thiazol-2-yl)-4,5-dihydro-1H-imidazole-2-carboxamides - Volodymyr Ya Horishny; Iryna V Drapak; Taras I Chaban; Yuriy V Ostapiuk; Vasyl S Matiychuk (Universitas Gadjah Mada, 2020)
New N-(5-R-benzyl-1,3-thiazol-2-yl)-2-morpholin-4-yl-2-oxoacetamides have been prepared in good yields via the reaction of N-(5-R-benzyl-1,3-thiazol-2-yl)-2-chloroacetamides with sulfur and morfoline. These compounds react with ethendiamine to form a series of novel N-[5-R-benzyl)-1,3-thiazol-2-yl]-4,5-dihydro-1H-imidazole-2-carboxamides with excellent yields. Anticancer activity screening of synthesized compounds was carried out within the framework of the Developmental Therapeutic Program of the National Cancer Institute's (DTP, NCI, Bethesda, Maryland, USA). It was shown that compounds are promising for new anticancer agents' search.